Tantangan Politik di Indonesia Tahun 2024: Membangun Kepemimpinan Pendidikan Islam - Sihono, Sihono (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to present a new perspective on understanding Islamic educational leadership in a dynamic political era, focusing on the political challenges faced by Indonesia in 2024 and how Islamic leadership can anticipate and respond to these challenges.Method – The research method employs a literature review with a critical analysis approach, with data collected from sources such as books, articles, previous studies, and relevant documents.Findings – The research findings identify two main challenges faced by Indonesia in 2024: political polarization and the spread of hoaxes and hate speech. The phenomenon of political polarization involves division among pluralist and Islamic groups, while hoaxes and hate speech affect the integrity and the democratic process. The discussion highlights the importance of effective Islamic educational leadership in addressing these political challenges by reinforcing moderate and tolerant Islamic values and instilling critical thinking skills and digital literacy in the younger generation. Research Implications – The implications of this research underscore the need for Islamic educational leaders who can adapt to the dynamics of politics and society and play a crucial role in shaping a generation capable of critical thinking and facing contemporary challenges wisely.